Synthesis and properties of poly(arylene ether)s based on 3-pentadecyl 4,4'-biphenol - Tawade, Bhausaheb V.; Shaligram, Sayali V.; Valsange, Nitin G.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Polymer International, 2016)
A new biphenol, 3-pentadecyl 4,4-biphenol, was synthesized starting from 3-pentadecylphenol and was polycondensed with 4,4-difluorobenzophenone, 1,3-bis(4-fluorobenzoyl)benzene and bis(4-fluorophenyl)sulfone to obtain poly(arylene ether)s with biphenylene linkages in the backbone and pendent pentadecyl chains. Inherent viscosities and number-average molecular weights (M-n) of the poly(arylene ether)s were in the range 0.50 - 0.81 dL g(-1) and 2.2 x 10(4) - 8.3 x 10(4), respectively. Detailed NMR spectroscopic studies of the poly(arylene ether)s indicated the presence of constitutional isomerism which existed because of the non-symmetrical structure of 3-pentadecyl 4,4-biphenol. The poly(arylene ether)s readily dissolved in common organic solvents such as dichloromethane, chloroform and tetrahydrofuran and could be cast into tough, transparent and flexible films from their chloroform solutions. The poly(arylene ether)s exhibited T-g values in the range 35-60 degrees C which are lower than that of reference poly(arylene ether)s without pentadecyl chains. The 10% decomposition temperatures (T-10) of the poly(arylene ether)s were in the range 410-455 degrees C indicating their good thermal stability. A gas permeation study of poly(ether sulfone) containing pendent pentadecyl chains revealed a moderate increase in permeability for helium, hydrogen and oxygen. However, there was a large increase in permeability for carbon dioxide which could be attributed to the internal plasticization effect of pendent pentadecyl chains. (c) 2016 Society of Chemical Industry
Keywords: cashew nut shell liquid (CNSL); gas permeation study; pentadecyl; poly(arylene ether)s; thermal stability

Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability

New pyrene cored small organic molecule with a flexible alkyl spacer: a potential solution processable blue emitter with bright photoluminescence - Valsange, Nitin G.; Wong, F. L.; Shinde, Durgaprasad; Lee, C. S.; Roy, V. A. L.; Manzhos, Sergei; Feron, K.; Chang, Samuel; Katoh, Ryuzi; Sonar, Prashant; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2017)
A new pyrene cored small organic molecule viz. 1,3,6,8-tetrakis(4-((5-(9H-carbazol-9-yl) pentyl)oxy) phenyl)pyrene (PY-II) was designed and synthesized. The carbazole moiety with an alkyl spacer was introduced at 1, 3, 6 and 8 positions of the pyrene core to improve the charge transport properties and solution processability. PY-II exhibited excellent solubility in common organic solvents and high thermal stability up to 345 degrees C. The photoluminescence quantum yield (PLQY) of PY-II in solution was found to be 0.9 with bright blue emission near 450 nm which is just appropriate for the human eye. The solution processed non-doped OLED device fabricated using PY-II as an emissive layer afforded a pure blue emission with CIE coordinates of 0.16 and 0.16, a power efficiency of 0.17 lm W-1, a maximum current efficiency of 0.41 cd A(-1) and a maximum brightness of 202 cd m(-2).

Synthesis and characterization of polyhydrazides and poly(1,3,4-oxadiazole)s containing multiple arylene ether linkages and pendent pentadecyl chains - Tawade, Bhausaheb V.; Valsange, Nitin G.; Wadgaonkar, Prakash P. (High Performance Polymers, 2017)
A new diacylhydrazide monomer, namely, 4-(4-(4-(4-(hydrazinocarbonyl)phenoxy)-2-pentadecylphenoxy)phenoxy) benzohydrazide (HPPDPB), was synthesized starting from 4-(4-hydroxyphenoxy)-3-pentadecylphenol. HPPDPB was polycondensed with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50:50 mol%) to obtain polyhydrazides containing multiple arylene ether linkages in the backbone and pendent pentadecyl chains. Polyhydrazides were subsequently cyclized in the presence of phosphorus oxychloride to obtain the corresponding poly(1,3,4-oxadiazole)s. Polyhydrazides and poly(1,3,4-oxadiazole)s exhibited inherent viscosities in the range 0.65–0.72 dL g−1 and 0.54–0.62 dL g−1, respectively, which indicated the formation of reasonably high-molecular weight polymers. Polyhydrazides were soluble in polar aprotic solvents such as N,N-dimethylformamide, N,N-dimethylacetamide (DMAc), 1-methyl-2-pyrrolidinone and pyridine whereas poly(1,3,4-oxadiazole)s exhibited excellent solubility even in common organic solvents such as chloroform, dichloromethane and tetrahydrofuran. Tough, transparent and flexible films of polyhydrazides and poly(1,3,4-oxadiazole)s could be cast from DMAc and chloroform solutions, respectively. X-Ray diffraction studies revealed amorphous nature of polyhydrazides and poly(1,3,4-oxadiazole)s and the formation of layered structure was observed due to ordered packing of pentadecyl chains. The 10% decomposition temperature (T 10) values for poly(1,3,4-oxadiazole)s were in the range 425–440°C indicating their good thermal stability. Glass transition temperature (T g) values of polyhydrazides and poly(1,3,4-oxadiazole)s were in the range 175–192°C and 92–103°C, respectively. The excellent solubility characteristics and the large gap between T g (92–103°C) and T 10 (425–440°C) values give poly(1,3,4-oxadiazole)-containing pendent pentadecyl chains better opportunities for processability.